Jurisprudential Analysis of Applicant Subordination in the Declaratory Death System - Zeng, Haijun (International Journal of Social Sciences and Public Administration, 2024)
The system of declaration of death leads to a series of changes in civil legal relations, such as the annihilation of marital relations and the creation of inheritance. China's civil code stipulates that can apply for the declaration of natural person's death for the interested party, but have the right to apply for the declaration of death of the order of the interested party is still debated in the academic community, the controversy lies in the applicant should have the order of the applicant. This paper analyzes the jurisprudence on whether the applicant for the declaration of death should have the right of precedence, and finds that the focus of the debate on the right of precedence is on the protection of property rights and interests or identity rights and interests, and finally proposes that the identity relationship of spouses be separated from the property relationship in the declaration of death, and that the declaration of disappearance be made as a pre-procedure of the declaration of death, in order to protect the legitimate interests of the interested parties.